The Effectiveness of Ethnomathematics-Based Problem Based Learning (PBL) Model on Junior High School Students' Mathematical Problem-Solving Ability - Asti, Maria Angelina; Wewe, Melkior; Bela, Maria Editha; Tali Wangge, Maria Carmelita; Sayuningsi A. E. Sartika (Universitas Islam Negeri Raden Intan Lampung, 2026)
The persistent challenge of developing students’ mathematical problem-solving ability highlights the need for instructional approaches that move beyond procedural learning toward meaningful and contextually grounded understanding. This study investigates the effectiveness of integrating ethnomathematics within a Problem-Based Learning (PBL) framework to enhance students’ mathematical problem-solving ability. A quasi-experimental design with a nonequivalent control group was employed involving 64 ninth-grade students at SMP Negeri 1 Bajawa, Indonesia. The experimental group was taught using ethnomathematics-based PBL, while the control group received conventional instruction. Data were collected through validated essay-based tests and analyzed using descriptive statistics and an independent samples t-test. The findings reveal that the experimental group achieved a substantially higher mean posttest score (84.06) compared to the control group (72.44), with the difference proven to be statistically significant (p < 0.05). Furthermore, the large effect size indicates that the intervention produced not only statistical significance but also meaningful educational impact. These results suggest that the integration of cultural context within a structured problem-based learning environment facilitates deeper cognitive engagement, enabling students to interpret, represent, and solve mathematical problems more effectively. The study advances existing literature by demonstrating that ethnomathematics functions as a cognitive catalyst when embedded within inquiry-driven pedagogy, rather than as a supplementary contextual element. In conclusion, ethnomathematics-based PBL offers a robust and contextually responsive instructional model that supports the development of higher-order thinking skills and provides a viable pathway for improving the quality of mathematics education.